PRAKTIK KOMUNIKASI PUBLIK DALAM PLATFORM PELAPORAN DIGITAL PEMERINTAH KOTA SEMARANG : STUDI KASUS LAPOR SEMAR - Indiera Permata Rusadi; Wijayanto Wijayanto (Journal of Politic and Government Studies, 2026)
This study aims to analyze digital public communication practices between the government and citizens through the Lapor Semar reporting platform in Semarang City. Existing e-government evaluations predominantly emphasize technical and administrative indicators, while the communicative dimension as a relational space between the state and citizens remains underexplored. This research employs a qualitative case study approach. Data were collected through in-depth interviews with government officials and platform users, supported by document analysis, and analyzed using the Miles and Huberman model. The analytical framework is based on Peter Dahlgren’s Civic Culture, encompassing the dimensions of knowledge, values, practices, trust, and spaces. The findings indicate that communication practices within Lapor Semar are primarily shaped by administrative rationality oriented toward technical problem resolution. The knowledge and practices dimensions operate procedurally, while values and trust depend largely on bureaucratic responsiveness. The spaces dimension reflects a semi-structured and pragmatic communication environment. The study concludes that although Lapor Semar functions effectively as a complaint management tool, it has not fully developed into a deliberative and substantive digital public communication space.